THE ABUNDANCE OF PLANKTONIC DIATOMS WITH THE NITRATE AND PHOSPHATE AROUND KUALA ENOK OF INDRAGIRI HILIR REGENCY OF RIAU PROVINCE - Hari Handika Sektiawan; Bintal Amin; Yusni Ikhwan Siregar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT Diatoms are the largest phytoplankton group and as the primary producer in marine waters.  This research was conducted in December 2017  around Kuala Enok of Indragiri Hilir Regency of Riau Province. The aim of this research was to determine the abundance of planktonic diatoms and their relationships with the nitrate and phosphate and to determine water quality as well as to see the relationship of planktonic diatoms abundance with water quality.  The survey method was applied in this research and sampling location determined by purposive sampling. Measurement of water quality was done by in situ and ex situ which consist of biologycal, physical and chemical parameters. Nitrate concentrations in waters ranged from 0,2207 to 0,2615 mg/l and phosphate concentrations ranged from 0,1595 to 0,2886 mg/l.  The planktonic diatoms on the water level in Kuala Enok consist of 11 genera and the abundance ranged from 6593,51 to 12336,24 individual/L, the mean value of diversity index ranged from 1,2074 to 1,6124. The dominance index ranged from 0,3767 to 0,5184 and the uniformity index value ranged from 0,6944 to 0,7955. Meanwhile, the correlation of diatom abundance with concentration of nitrate was 0,14 (very weak relationship) and correlation of diatomic abundance with phosphate concentration was 0,13 (very weak relationship). Based on the result of the abundance of planktonic diatoms with the nitrate and phosphate calculation on water level can be concluded that the waters in Kuala enok was in medium contaminated condition. Keyword: The abundance, nitrate and phosphate, planktonic diatom, Kuala Enok